2007
DOI: 10.1002/ps.1359
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and feeding deterrence of crude toxin extracts of Lecanicillium (Verticillium) lecanii (Hyphomycetes) against sweet potato whitefly, Bemisia tabaci (Homoptera: Aleyrodidae)

Abstract: Crude toxins [toxin(V3450) and toxin(Vp28,) extracted from Lecanicillium (Verticillium) lecanii (Zimmermann) Gams & Zare strain V3450 and Vp28 respectively] were tested for contact toxicity, feeding deterrence and repellent activity against the sweet potato whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae). Both toxins showed ovicidal activity to eggs, with LC(50) values of 447 and 629 mg L(-1) respectively. Nymphs of B. tabaci were the most susceptible stages (LC(50) values were calculated at 111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 22 publications
(35 reference statements)
1
21
0
5
Order By: Relevance
“…Andrew et al (2008) found mortality of B. tabaci was significantly different between different isolate varying from 87-56%. Wang et al (2007) showed that nymph was the most susceptible stage and adult being the second, this result supports the present study. The result was supported by (Cuthbertson et al 2005) where nymphs were found to be the most susceptible.…”
Section: Fig 1 Layout Of the Experiments Designsupporting
confidence: 92%
“…Andrew et al (2008) found mortality of B. tabaci was significantly different between different isolate varying from 87-56%. Wang et al (2007) showed that nymph was the most susceptible stage and adult being the second, this result supports the present study. The result was supported by (Cuthbertson et al 2005) where nymphs were found to be the most susceptible.…”
Section: Fig 1 Layout Of the Experiments Designsupporting
confidence: 92%
“…Crude protein extracts from 25 fungal isolates, including M. anisopliae and B. bassiana cultured in AD exhibited different toxicity to moth larvae and lost its activity after exposure to high temperature and protease [10]. Crude toxin extracted from L. lecanii killed eggs, nymphs, and adults of sweet potato whitefly and also showed antifeedant activity [11]. The supernatant of an isolate of B. bassiana contained chitinase and degraded haemocoel of cotton aphids [7].…”
Section: Discussionmentioning
confidence: 99%
“…Production of metabolites and their control efficacy against mosquitoes differed among fungal isolates and culture media or media composition [6]. Culture filtrates of entomopathogenic fungi such as Lecanicillium lecanii and B. bassiana reduce aphid survival rates [7-9] and deter feeding by whitefly and larva of Spodoptera littoralis [10, 11]. These culture filtrates may include various enzymes, such as protease, chitinase, and lipase, which are important in the process of infection by conidia.…”
mentioning
confidence: 99%
“…In recent years, many researchers have interested in natural products extracted from plants or microorganisms as alternatives to conventional chemical insecticides to use them in integrated pest management programs (IPM). Wang et al (2007) mentioned that the entomopathogenic fungi able to secrete a wide range of bioactive compounds known as secondary metabolic compounds as well as the fungal metabolites have been shown to possess the potential insecticidal activity and may be used as biopesticides. Pampapathy et al (2011) reported that metabolites in culture filtrates and mycelial extracts of B. bassiana significantly reduced the survival of A. gossypii and the number of aphids settling on the treated leaf discs.…”
Section: Insecticidal Activity Of Secondary Metabolites Of Isolated Fmentioning
confidence: 99%